Starry messenger : cosmic perspectives on civilization [compact disc, unabridged] - Tyson, Neil deGrasse (Macmillan Audio, 2022)
In a time when our political and cultural perspectives feel more polarized than ever, Neil deGrasse Tyson provides an antidote to so much of what divides us: a cosmic perspective and the rationality of science.